PENDEKATAN HERMENEUTIKA AL-QUR’AN KONTEMPORER NASHR HAMID ABU ZAID - Zayyadi, Ahmad (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2017)
The controversial thoughts of Nasr Hamid Abu Zayd provide enough variation and inspiration for the development of religious thought, especially regarding the hermeneutical theory applied in the gender discourse and women discussed in this article. In general, his hermeneutical theory of Abu Zayd is more critical of the study of the Qur'an as a